SHARING SESSION PENDIDIKAN ANAK DI ERA DIGITAL: MEMBANGUN SIKAP BIJAK DALAM PENGGUNAAN TEKNOLOGI - Andromeda Valentino Sinaga; Rimma Sianipar; Muhammad Isnawan Syafir; Kartini Kartini; Fauziah Fauziah (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The rapid growth of digital technology has profoundly influenced children, shaping their cognitive, social, and emotional development. Technology offers many benefits, such as greater access to information and learning opportunities. However, poor supervision can lead to numerous problems, including screen addiction, social issues, and mental health disorders. This community service project was designed to educate parents on both the positive and negative impacts of digital technology in children's lives and to equip them with the skills needed to guide their children toward healthy technology use. Teaching sessions, case-based training, and interactive forums formed the core of the program's curriculum. To evaluate the program’s effectiveness, we conducted interviews and surveys with participants to assess changes in their knowledge and how effectively they applied the strategies taught. The results were encouraging: parents showed increased awareness of the impact of digital media on their children's lives and gained better control over the amount of screen time their children spent. Overall, the program successfully raised parental awareness about the importance of actively assisting and guiding children in the use of technology.